Federal travel restrictions to prevent disease transmission in the United States: An analysis of requested travel restrictions. Issue 18 (July 2017) - Jungerman, M. Robynne; Vonnahme, Laura A.; Washburn, Faith; Alvarado-Ramy, Francisco
Abstract: Background: Individuals with certain communicable diseases may pose risks to the health of the traveling public; there has been documented transmission on commercial aircraft of tuberculosis (TB), measles, and severe acute respiratory syndrome (SARS). Federal public health travel restrictions (PHTR) prevent commercial air or international travel of persons with communicable diseases that pose a public health threat. Methods: We described demographics and clinical characteristics of all cases considered for PHTR because of suspected or confirmed communicable disease from May 22, 2007, to December 31, 2015. Results: We reviewed 682 requests for PHTR; 414 (61%) actions were completed to place 396 individuals on PHTR. The majority (>99%) had suspected (n = 27) or confirmed (n = 367) infectious pulmonary TB; 58 (16%) had multidrug-resistant-TB. There were 128 (85%) interceptions that prevented the initiation or continuation of travel. PHTR were removed for 310 (78%) individuals after attaining noninfectious status and 86 (22%) remained on PHTR at the end of the analysis period. Conclusions: PHTR effectively prevent exposure during commercial air travel to persons with potentially infectious diseases. In addition, they are effective tools available to public health agencies to prevent commercial travel of individuals with certain communicable diseases and possibly reconnect them with public health authorities.